When Causal Specificity Does Not Matter (Much): Insights from HIV Treatment. Issue 4 (December 2019) - Neal, Jacob P.
Abstract : Philosophers of biology generally agree that causal specificity tracks biological importance: more specific causes are more important. I argue that this correlation does not hold in much research aimed at biomedical intervention. Applying James Woodward's analysis of causal specificity to the development and design of HIV treatments, I show that drugs that are less causally specific produce better therapeutic outcomes and are more highly valued. Thus, I conclude that the importance of biological causes does not track their specificity but instead varies depending on the biological practice we consider and the goals of that practice.